Industrial Sewage Water Cleaning in Oil and Gas Mining Complexes - Kalyuzhniy, Anatoliy; Savyk, Vasyl; Molchanov, Petro; Syzonenko, Anatoliy (International Journal of Engineering and Technology, 2018)
The state of existing water drainage cleaning systems of separated oil and gas mining complexes and observed it relying on the example of cleaning household sewage water with correspondence to ecological and sanitary requirements of water drainage systems has been analyzed. The methodology to clean household sewage water on separated units of oil and gas mining complexes Â has been produced. While reconstructing water drainage systems of these complexes, there has been offered to use the pre-cleaning of sewage water applying special filters and self-cleaning ability of soil that lets introduce the system of water drainage without direct throwing to water sources. There has been shown the example of calculation of filtration wells-absorbers with underground filtration fields and drawings of the general plan of sewerage cleaning systems, pre-cleaning filters and mixed underground filtration fields.Â